Taxation, Inequality, and the Illusion of the Social Contract in Brazil - Nogueira, José Ricardo; Siqueira, Rozane Bezerra; Luna, Carlos Feitosa (Pesquisa & Debate Revista do Programa de Estudos Pós-Graduados em Economia Política, 2015)
Brazil combines high inequality and high tax yield as percentage of the GDP. This situation contradicts the predictions of two central theories of taxation and democratic politics. The first theory predicts that, within a democratic context, high levels of income inequality should lead governments to carry out significant redistribution. The second theory sees the government’s ability to raise tax revenue as dependent on a social contract between the state and its citizens, and predicts a negative relationship between taxation and social polarization. In this paper, we propose that the theory of fiscal illusion can account for this double puzzle.